Using Correlation Analysis to Examine the Impact of Covid-19 Pandemics on Various Socioeconomic Aspects: Case study of Indonesia - Fitriadi, Fitriadi; Jiuhardi, Jiuhardi; Busari, Arfiah; Ulfah , Yana; Permadi Hakim, Yundi; Kurniawan A., Erwin; Darma, Dio Caisar (Geographica Pannonica, 2022)
This paper diagnoses the determination of Covid-19 on economic and social aspects in Indonesia. Panel data collected from 34 provinces in Indonesia for the 2020-2023 period supports the quantitative method. Three analyzes (Spearman, Kendall, and Pearson) were used to measuring the relationship and its partial effect. Research findings indicate that Covid-19 cases have a negative impact on labor productivity, migration, domestic violence, and sexual harassment. From other results, per capita spending, well-being, unemployment, and poverty actually increased when there was a surge in Covid-19. For the Spearman rho correlation, with a degree of 1 percent (p < 0.01), there is a significant effect between capita spending on well-being, per capita spending and well-being on migration, and poverty on labor productivity. Tested by Kendall’s tau and Pearson, the Covid-19 tragedy positively affected per capita spending, well-being, unemployment, poverty, and mortality, but labor productivity, migration, domestic violence, and sexual harassment were negatively affected by Covid-19. The partial probability level (p < 0.05 and p < 0.01) reveals a significant effect of per capita spending on well-being, migration on per capita spending and well-being, and poverty on labor productivity. Although per capita spending has a significant impact on well-being (5 percent confidence level), there is a slight difference from the Pearson test, where with a tolerance limit of 1 percent, poverty affects sexual harassment significantly. Covid-19 has taught many things, so that humanity does not disappear with conditions that seek peace. Policy makers need to schedule a more inclusive national and regional resilience system.
Keywords: Social; economy; Covid-19; Correlation; panel data